PENOLAKAN ITHBAT NIKAH SIRI BAGI ‎SUAMI YANG SUDAH BERISTRI ‎ - muhammad roqib (State Islamic University (UIN) of Sunan Ampel, 2016)
Abstract: This study reviews the judge’s legal consideration basis in rejecting the confirmation of unregistered marriage (isbat nikah) for a husband who had married in the Religion Court’s decision of Nganjuk No: 1339/Pdt.G/2013/PA.Ngj and how the analysis of Islamic law against the denial of the confirmation of unregistered marriage for a husband who had married in the Religious Court’s decision of Nganjuk. The data of the research are obtained through documentation and interview. The data are then analyzed by descriptive-deductive mindset. This study concludes that the consideration and the legal basis used by the judge in the case of the confirmation of unregistered marriage is Article 4, paragraph 1 of Law No. 1 of 1974 About Marriage jo. Article 52 paragraph 1 Islamic Law Compilation. In Article 5, paragraph 1 (a) of Law No. 1 of 1974 jo. Article 58, paragraph 1 (a) Islamic Law Compilation states that one of the requirements of conducting polygamy is the condition must be approved by wife. The judge rejected the request of the confirmation of unregistered marriage because in this case, according to the judge, is classified as polygamy. Judge just looks at the judicial aspect without considering the principles of maqasid al-shari’ah. In this case, the very important to note is the civil right and welfare of children which is one of the main constituents of hifzd al-nasl (protection of children) that should be maintained. In consideration of hifzd al-nasl, the petition of the confirmation of unregistered marriage should have been granted.Abstrak: Penelitian ini mengkaji tentang dasar pertimbangan hukum hakim dalam menolak ithbat nikah siri bagi suami yang sudah beristri dalam putusan Pengadilan Agama Nganjuk nomor: 1339/Pdt.G/2013/ PA.Ngj dan bagaimana analisis hukum Islam terhadap penolakan ithbat nikah siri bagi suami yang sudah beristri dalam putusan Pengadilan Agama Nganjuk tersebut. Data penelitian ini diperoleh melalui dokumentasi dan wawancara yang selanjutnya dianalisis dengan metode deskriptif menggunakan pola pikir deduktif. Penelitian ini berkesimpulan bahwa, pertimbangan dan dasar hukum yang digunakan hakim dalam menetapkan perkara ithbat nikah adalah pasal 4 ayat 1 Undang-Undang No 1 Tahun 1974 Tentang Perkawinan jo. Pasal 52 ayat 1 Kompilasi Hukum Islam. Dalam pasal 5 ayat 1 (a) Undang-Undang No 1 Tahun 1974 jo. Pasal 58 ayat 1 (a) Kompilasi Hukum Islam bahwa salah satu syarat berpoligami harus ada persetujuan dari istri. Hakim menolak permohonan ithbat nikah karena pada kasus ini menurut majelis hakim tergolong perkara poligami. Hakim hanya melihat dari aspek yuridis tanpa mempertimbangkan maqasid al-shari’ah. Dalam kasus ini yang sangat penting untuk diperhatikan adalah hak-hak keperdataan dan kesejahteraan anak yang merupakan salah satu unsur pokok hifzu al-nasli yang harus terpelihara. Dengan pertimbangan tersebut permohonan ithbat nikah ini seharusnya dikabulkan.Kata Kunci: ithbat nikah dan nikah sirri